Preparation method and application of biochar-loaded Fe2C composite material
By mixing the crop straw with iron salt solution, biochar-loaded Fe2C composite material is prepared, which solves the problem of limited adsorption capacity of existing biochar, and achieves efficient adsorption of heavy metals and efficient preparation of materials.
Patent Information
- Application Number
- CN202411748726.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing biochar has limited adsorption capacity of heavy metals and has a low single production yield, making it difficult to meet the needs of large-scale applications.
After pyrolyzing the crop straw, it is mixed with the iron salt solution, stirred and soaked, then dried and sieved, and finally heated in a tube furnace to prepare a biochar-loaded Fe2C composite material.
The adsorption performance of biochar to heavy metals is significantly improved, especially for Cu, and can be efficiently prepared under laboratory conditions, increasing the specific surface area and adsorption site of the material.
Smart Images

Figure CN119500068A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of water remediation material preparation, and in particular to a preparation method and application of a biochar-loaded Fe2C composite material. Background Art
[0002] Heavy metals in water environments (such as Pb, Cu, Ni, Co, and Zn) have the characteristics of persistent pollution and non-degradability, and can exist in nature for a long time. Heavy metals can accumulate in the food chain, affect the growth and development of organisms, and seriously threaten human health. With the increasing attention paid to public health safety and environmental quality, scientists have successively developed methods such as chemical precipitation, ion exchange, electrolysis, membrane separation, coagulation-flocculation and adsorption to remove heavy metal ions in water environments. Among them, the adsorption method is widely used because of its good removal effect on low-concentration metal ions and its economical and affordable.
[0003] Crop straw has been proven to be one of the raw materials for preparing biochar. Straw biochar has the advantages of easily replaceable surface, porous structure and controllable chemical properties. It is environmentally friendly and a green adsorbent. However, the small particle size of biochar and its limited adsorption capacity for metal ions limit the large-scale application of biochar. In view of the above problems, it is urgent to modify straw biochar to improve its ability to adsorb metal ions.
[0004] Many studies have found that biochar can be loaded with Fe through pyrolysis and impregnation. 0 and Fe3C, etc., to improve the adsorption and removal capacity of biochar for heavy metals. However, few studies have found that biochar is loaded with Fe2C. At the same time, under laboratory conditions, the output of a single preparation of iron-based biochar materials is very limited. Therefore, the development of a material and technology that can efficiently prepare biochar-loaded Fe2C under laboratory conditions is a key issue that needs to be solved urgently.
[0005] Patent No. CN202311682343 states: "Wash, chop and dry the rice husk, put it into an anaerobic tube furnace, pyrolyze it at a high temperature of 450°C for 4 hours, and grind it through a 100-mesh sieve after cooling to obtain biochar that has passed the 100-mesh sieve; weigh 20g of granular NaOH, 20g of Na2S2O4 and 5g of biochar that has passed the 100-mesh sieve in a glove box, mix them evenly to obtain a solid mixture; S2. In the glove box, mix 20g of ferrous chloride (FeCl2) on a stirring bar. The mixture was added to the solid mixture under the condition of 0-10℃ ice bath, stirred evenly and reacted for 2 minutes, then placed in an ice bath at 0-10℃, 25mL of deionized water was sprayed into the solid mixture with a spray pot, the flow rate of deionized water was 10mL / min, and stirred while spraying, so that the reactants reacted in the rheological phase; finally, a nano zero-valent iron-ferroferric oxide composite biochar material was prepared, and at a dosage of 0.1%, the adsorption rate of the Pb-containing solution with a concentration of 30mg / L reached 70%. However, the single preparation yield of this technology is low, and the adsorption effect needs to be improved. Summary of the invention
[0006] The main purpose of the present invention is to provide a preparation method and application of a biochar-loaded Fe2C composite material, to prepare a biochar-loaded Fe2C composite material, which has better adsorption performance for heavy metals and good selectivity for Cu.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is: a method for preparing a biochar-loaded Fe2C composite material, which specifically comprises the following steps:
[0008] Step S1, air-drying and crushing the crop straw, putting it into an iron can, sealing it and putting it into a muffle furnace, heating it to a predetermined temperature at a certain heating rate and keeping it for a period of time for pyrolysis;
[0009] Step S2, grinding and sieving the pyrolysis product to obtain biochar;
[0010] Step S3, mixing the biochar and the iron salt solution in a certain mass ratio, stirring them fully, and soaking them for a period of time;
[0011] Step S4, drying and sieving the product obtained in step S3;
[0012] Step S5, placing the product obtained in step S4 into a tube furnace and heating the temperature to a predetermined temperature at a certain heating rate, and maintaining the temperature for a period of time;
[0013] Step S6, grinding and sieving the product obtained in step S5 to obtain the biochar-loaded Fe2C composite material.
[0014] Preferably, in step S1, the heating rate is 8-12°C / min, the predetermined temperature is 250-400°C, and the holding time is 1-3h.
[0015] Preferably, in step S3, the mass ratio is 1:3 to 1:6;
[0016] Preferably, in step S5, the heating rate is 8-12°C / min, the predetermined temperature is 500-800°C, and is maintained for 1-3h.
[0017] The present invention also provides an application of a biochar-loaded Fe2C composite material in adsorbing heavy metals.
[0018] Preferably, the heavy metal includes one or more of Pb, Cu, Co, Ni and Zn.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The carbon raw material of the composite material of the present invention adopts crop straw, which realizes the reuse of straw and is more environmentally friendly. The biochar-loaded Fe2C composite material of the present invention can enhance the electrostatic interaction, π-π interaction, coprecipitation and ion exchange capacity of the straw biochar by introducing Fe(II), Fe(III), Fe(0) or iron-containing minerals in an exogenous form, and improve the specific surface area and adsorption sites of the biochar, which can significantly improve the performance of the straw biochar in removing heavy metals in the water environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 , X-ray diffraction pattern of biochar-loaded Fe2C composite;
[0022] Figure 2 , SEM images of biochar-loaded Fe2C composites;
[0023] Figure 3 , N2 adsorption and desorption isotherms on biochar-loaded Fe2C composites
[0024] Figure 4 , adsorption kinetics of heavy metals on biochar-loaded Fe2C composites;
[0025] Figure 5 , adsorption isotherms of heavy metals on biochar-loaded Fe2C composites;
[0026] Figure 6 , adsorption effect diagram of biochar-loaded Fe2C composite materials under single and composite metal systems;
[0027] Figure 7, Comparison of the adsorption effects of biochar-loaded Fe2C composite materials and reference materials under the same experimental conditions. DETAILED DESCRIPTION
[0028] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0029] A method for preparing a biochar-loaded Fe2C composite material comprises the following steps:
[0030] Step S1, air-drying and crushing the crop straw, placing it in an iron can, sealing it and placing it in a muffle furnace, heating it to 250-400° C. at a heating rate of 8-12° C. / min and maintaining it for 1-3 hours for pyrolysis;
[0031] Step S2, grinding and sieving the pyrolysis product to obtain biochar;
[0032] Step S3, mixing the biochar with ferrous sulfate or ferric chloride solution at a mass ratio of 1:3 to 1:6, fully stirring, and soaking for 8 to 24 hours;
[0033] Step S4, drying and sieving the product obtained in step S3;
[0034] Step S5, placing the product obtained in step S4 into a tube furnace and heating the temperature to 500-800° C. at a heating rate of 8-12° C. / min, and maintaining the temperature for 1-3 h;
[0035] Step S6, grinding and sieving the product obtained in step S5 to obtain the biochar-loaded Fe2C composite material.
[0036] The biochar-loaded Fe2C composite material can be used as an adsorbent to adsorb heavy metals in water, wherein the heavy metals are one or more of Pb, Cu, Co, Ni and Zn, and the addition amount of the adsorbent is 0.5 g / L.
[0037] Embodiment 1
[0038] Step S1, air-drying and crushing the corn stalks, placing them in an iron can, sealing them and placing them in a muffle furnace, heating them to 300° C. at a heating rate of 10° C. / min and maintaining them for 1 h for pyrolysis;
[0039] Step S2, grinding the product obtained in step S1 and passing it through a 40-mesh sieve to obtain raw biochar (BC);
[0040] Step S3, dissolve 210 g of ferrous sulfate in pure water, dilute to 500 mL, mix 45 g of BC with the ferrous sulfate solution, stir at a constant speed on a magnetic stirrer and fully immerse for 12 h;
[0041] Step S4, placing the product obtained in step S3 in an oven at 105° C. for 48 hours until dry, and grinding it through a 100-mesh sieve;
[0042] Step S5, placing the product obtained in step S4 into a quartz boat, loading it into a tube furnace, heating it to 700° C. at a heating rate of 10° C. / min and maintaining it for 1 hour;
[0043] Step S6: Grind and sieve the product obtained in step S5 to obtain a biochar-loaded Fe2C composite material, recorded as (LCF), and place the obtained material in a vacuum drying oven for later use.
[0044] Embodiment 2
[0045] Step S1, air-drying and crushing the corn stalks, placing them in an iron can, sealing them and placing them in a muffle furnace, heating them to 300° C. at a heating rate of 10° C. / min and maintaining them for 1 h for pyrolysis;
[0046] Step S2, grinding the product obtained in step S1 and passing it through a 40-mesh sieve to obtain raw biochar (BC);
[0047] Step S3, dissolve 230g of ferrous sulfate in pure water, dilute to 500mL, mix 45g of BC with the ferrous sulfate solution, stir at a constant speed on a magnetic stirrer and fully immerse for 12h;
[0048] Step S4, placing the product obtained in step S3 in an oven at 105° C. for 48 hours until dry, and grinding it through a 100-mesh sieve;
[0049] Step S5, placing the product obtained in step S4 into a quartz boat, loading it into a tube furnace, heating it to 700° C. at a heating rate of 10° C. / min and maintaining it for 1 hour;
[0050] Step S6: Grind and sieve the product obtained in step S5 to obtain a biochar-loaded Fe2C composite material, recorded as (HCF), and place the obtained material in a vacuum drying oven for later use.
[0051] Test Example 1: X-ray Diffraction (XRD) Characterization
[0052] XRD was used to evaluate the crystal changes of biochar-loaded Fe2C composites. Figure 1 As shown in the figure, both LCF and HCF have the diffraction peak of Fe2C (PDF#036-1249), indicating that Fe2C is successfully loaded on the biochar. At the same time, the composite material also has CFe 15.1 Diffraction peaks of Fe7SiO 10 The diffraction peaks of Fe(PDF#022-1118) and 2.95 Si 0.05The diffraction peak of O4 (PDF#052-1140) is due to the fact that corn stalks are rich in Si, so Si-containing iron oxides are generated.
[0053] Test Example 2: SEM Characterization
[0054] Scanning electron microscopy (SEM) was used to evaluate the carbon and iron distribution of biochar-loaded Fe2C composites. Figure 2 As shown in the figure, in both LCF and HCF, iron is evenly distributed on the material, and as the iron content increases, the iron element distributed on the material increases accordingly. The increase in Fe content may change the structure and size of Fe2C particles, thereby changing the overall properties of the material.
[0055] Test case 3: BET characterization
[0056] The specific surface area (BET) of the materials was characterized to evaluate the effect of different iron contents on the specific surface area of the materials. As shown in Table 1, the specific surface areas of LCF and HCF are 30.16 and 17.70 m 2 / g, the increase of iron content will reduce the specific surface area of the material, which may be due to the iron filling the pores of biochar to a certain extent. Figure 3 As shown, the N2 adsorption-desorption curves of LCF and HCF are both type IV, and the hysteresis loops are both type H4, indicating that both materials are mesoporous materials.
[0057] Table 1. BET surface area and pore morphology of materials
[0058] Test Example 4: Adsorption Kinetics Experiment
[0059] Accurately weigh 100 mg of HCF and LCF and place them in a 250 mL blue-capped bottle. Add 200 mL of 0.04 mM / L Pb, Ni, Co, Zn and Cu solutions (PbCl2, NiCl2·6H2O, CoCl2·6H2O, ZnCl2 and CuCl2·2H2O, pH of the solution is 5, adjusted with 0.1 M NaOH and HCl) respectively. Place on a thermostatic shaker and shake at 25°C at a speed of 180 rpm. Sampling was performed at 5, 30, 60, 120, 240, 480, 720, 960 and 1200 min, three times in parallel. After the shaking, the solution was filtered with a 0.22 μm filter head and tested on the machine. Figure 4 As shown in Table 2, the adsorption kinetics of the five metals were fitted. The results showed that the pseudo-second-order kinetic model was better than the pseudo-first-order kinetic model, and the fitting coefficient (R 2), therefore, chemical reaction may play a leading role in the removal process. Compared with LCF, HCF has a higher adsorption rate for Pb, while the opposite is true for Cu, which may be due to the fact that the relative ionic radius of Pb is closer to that of Fe, and there may be ion exchange. However, there is no significant difference in the adsorption rate of Ni, Co and Zn between HCF and LCF.
[0060] Table 2. Kinetic parameters of LCF and HCF for Pb, Ni, Co, Zn and Cu
[0061] Test Example 5: Adsorption Isotherm Experiment
[0062] Accurately weigh 100 mg of HCF and LCF respectively and place them in 250 mL blue-capped bottles, and add 200 mL of Pb, Ni, Co, Zn and Cu solutions of different concentrations (0.02 mM / L, 0.04 mM / L, 0.1 mM / L, 0.2 mM / L, 0.5 mM / L, 1 mM / L, 2 mM / L, 4 mM / L) respectively. The pH of the solution is 5 (adjusted with 0.1 M NaOH and HCl). Set up 3 parallels. Place on a thermostatic shaker and shake at 25 ° C at a speed of 180 rpm for 20 hours. After the shaking, the solution is filtered with a 0.22 μm filter head and tested on the machine. Figure 5 As shown in Table 3, the adsorption isotherm equations of the five metals were fitted. The results showed that the Langmuir isotherm adsorption model was better than the Freundlich isotherm adsorption model, indicating that HCF and LCF had uniform monolayer adsorption for Pb, Ni, Co, Zn and Cu. HCF and LCF had good adsorption effects on Pb and Cu, and their maximum adsorption amounts were 51.035, 47.373, 41.937 and 42.246, respectively.
[0063] Table 3. Adsorption isotherms of LCF and HCF for Pb, Ni, Co, Zn and Cu
[0064] Test Example 6: Multivariate Adsorption Experiment
[0065] Weigh 100 mg HCF and LCF respectively and place them in a 250 mL blue-cap bottle, add 200 mL of a mixed solution of Pb, Ni, Co, Zn and Cu with a concentration of 0.06 mM / L, set up 3 parallels, place them on a constant temperature shaker at 25°C and 180 rpm for 20 hours, filter the solution with a 0.22 μm filter head after the shaking, and test the sample on the machine. Figure 6As shown in the figure, at a concentration of 0.06 mM / L, HCF and LCF exhibit excellent selective adsorption for Pb and Cu, and the adsorption rate for Ni and Co is almost 0. This may be because in the mixed system, the adsorption sites on the material surface are more replaced by Pb and Cu.
[0066] Comparative Example
[0067] The nano zero-valent iron-ferroferric oxide composite material disclosed in the invention patent with publication number CN117654438A was used as a comparative material, as follows:
[0068] Weigh 200 mg HCF and LCF accurately and place them in 250 mL blue-capped bottles, add 200 mL of 30 mg / L Pb and Cu solutions respectively, set up 3 parallels, place them on a constant temperature shaker at 25 ° C and 200 rpm for 250 min, filter the solution with a 0.22 μm filter head after the shaking, and measure the sample on the machine. Add the nano zero-valent iron-ferroferric oxide composite material to 30 mg / L Pb and Cu solutions at a dosage of 0.1%, and the reaction time is 250 min. The adsorption rate of the 30 mg / L Pb-containing solution is 70%. Compared with the ones in this study, Figure 7 As shown, under the same experimental conditions, the adsorption rates of LCF and HCF for Pb were 99.4% and 98.5%, respectively, which were significantly better than those of the control examples. It can be seen that the material prepared in this study has excellent adsorption performance for Pb and has good application prospects.
[0069] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a biochar-loaded Fe2C composite material, characterized in that: The specific steps include: Step S1, air-drying and crushing the crop straw, putting it into an iron can, sealing it and putting it into a muffle furnace, heating it to a predetermined temperature at a certain heating rate and keeping it for a period of time for pyrolysis; Step S2, grinding and sieving the pyrolysis product to obtain biochar; Step S3, mixing the biochar and the iron salt solution in a certain mass ratio, stirring them fully, and soaking them for a period of time; Step S4, drying and sieving the product obtained in step S3; Step S5, placing the product obtained in step S4 into a tube furnace and heating the temperature to a predetermined temperature at a certain heating rate, and maintaining the temperature for a period of time; Step S6, grinding and sieving the product obtained in step S5 to obtain the biochar-loaded Fe2C composite material.
2. The method for preparing a biochar-loaded Fe2C composite material according to claim 1, characterized in that: In step S1, the heating rate is 8-12°C / min, the predetermined temperature is 250-400°C, and the holding time is 1-3h.
3. The method for preparing a biochar-loaded Fe2C composite material according to claim 1, characterized in that: In step S3, the mass ratio is 1:3 to 1:
6.
4. The method for preparing a biochar-loaded Fe2C composite material according to claim 1, characterized in that: In step S5, the heating rate is 8-12°C / min, the predetermined temperature is 500-800°C, and it is maintained for 1-3h.
5. Application of a biochar-loaded Fe2C composite material in the adsorption of heavy metals, wherein the biochar-loaded Fe2C composite material is prepared by the preparation method described in any one of claims 1 to 4.
6. The use of a biochar-loaded Fe2C composite material in adsorbing heavy metals according to claim 5, characterized in that: The heavy metal includes one or more of Pb, Cu, Co, Ni and Zn.
Citation Information
Patent Citations
Preparation method of nano zero-valent iron loaded hydrophilic porous biochar composite material
CN108722356A
Preparation method and application of biochar-loaded zero-valent iron material for removing Cd < 2 + > in water body
CN114618434A
Preparation method and application of charcoal-loaded clay mineral composite material
CN116099499A
Nanometer zero-valent iron-ferroferric oxide composite material as well as preparation method and application thereof
CN117654438A